2009
DOI: 10.1016/j.rmed.2008.11.019
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of pharmacological treatment of COPD in Spain

Abstract: Treatment of COPD allows for the identification of areas of inefficiency. An improvement in the adherence to the GOLD guidelines would imply potential savings of medication costs of about 20% of the observed costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
0
12
1
2
Order By: Relevance
“…Although the potential drug savings are of the same order, the difference in average drug cost between our study and a previous analysis [Miravitlles et al 2009a] may be due to the fact that, in our case, 92.5% of patients had an FEV 1 above 50%…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Although the potential drug savings are of the same order, the difference in average drug cost between our study and a previous analysis [Miravitlles et al 2009a] may be due to the fact that, in our case, 92.5% of patients had an FEV 1 above 50%…”
Section: Discussioncontrasting
confidence: 51%
“…To date, the only comparison made in our area between the GOLD recommendations and clinical practice looked at drug costs using a theoretical method [Miravitlles et al 2009a]. This study identified that the mean annual cost of drug treatment for a patient with COPD was €1218-1314 and the potential savings derived from adherence to the GOLD recommendations was on average between €198 and €293.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the demonstration of product value during drug development faces the limitations of clinical trial designs, which may lead to an underestimation of costs compared with what would occur in a more naturalistic setting, especially considering the small and highly selected fraction of the COPD patient population included in these trials [2,51]. Treatment guidelines in COPD are mainly based on evidence from the clinical trials conducted by the pharmaceutical industry.…”
Section: Economic Aspects Of Copd Pharmacological Treatmentsmentioning
confidence: 99%
“…5 Numerous Spanish and international observational studies performed in different care settings have detected intensive use of ICs alone or combined with LABD in COPD patients. In Spain, several studies [6][7][8] have shown that over 60% of patients with mild COPD receive ICs (alone or in combination with LABDs), generally at high doses, irrespective of the care setting. This is in stark contrast with studies indicating that the mixed COPD-asthma phenotype is identified in less than 20% of patients, 9 and that only one third of patients are frequent exacerbators.…”
Section: Introductionmentioning
confidence: 99%